THE EFFECTIVENESS OF APPLICATION OF POWER POINT MEDIA IN ARABIC LANGUAGE LEARNING TO IMPROVING STUDENT'S MUFRADAT - Arif Widodo; Dwi Wilianto (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2022)
This research aims to determine the effectiveness of the application of power point media to increase the mastery of mufradat. As a form of effort to improve skills in learning Arabic, especially in the mastery of mufrodat. So it takes a variety of methods and media that are varied and innovative. At this time information media technology has been able to make various ways to make it easier to convey information, such as power point media. This study uses an experimental method with the subject of this research is class VII MTs NU Karangploso Malang. The data were searched using observation, interview, documentation, test, and questionnaire techniques. The results of this study indicate the effectiveness of the power point media to increase the mastery of mufrodat students of class VII MTs NU Karangploso Malang in learning Arabic.